2012
DOI: 10.1590/s0103-50532012005000019
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic cordiaquinones from the roots of Cordia polycephala

Abstract: A investigação química das raízes de Cordia polycephala resultou no isolamento de duas novas naftoquinonas terpenoídicas, 6-[10-(12,12-dimetil-13α-(22-metil-21-butenoilóxi -[10-(12,12-dimetil-13α-(tigloilóxi)-16-metenilciclohexil)etil]-naftaleno-1,4-diona, designadas de cordiaquinonas N (1) e O (2), respectivamente. As cordiaquinonas já conhecidas, B (3), L (4) e E (5), foram também isoladas. Suas estruturas foram elucidadas após detalhada análise dos dados de RMN 1 H e 13 C (1D e 2D) e EMAR (espectrometria de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…[64][65][66][67][68][69] Cordiaquinones A, B, E, F, G, H, J and K were studied for antifungal and larvicidal activity. [61,67,70] Cordiaquinone J was found to be active against HL-60 and SF-295 cells with 2.7 lm and 6.6 lm IC 50 value, respectively, when screened for cytotoxicity study.…”
Section: Meroterpenoid Quinonesmentioning
confidence: 99%
See 3 more Smart Citations
“…[64][65][66][67][68][69] Cordiaquinones A, B, E, F, G, H, J and K were studied for antifungal and larvicidal activity. [61,67,70] Cordiaquinone J was found to be active against HL-60 and SF-295 cells with 2.7 lm and 6.6 lm IC 50 value, respectively, when screened for cytotoxicity study.…”
Section: Meroterpenoid Quinonesmentioning
confidence: 99%
“…Cordiaquinone A (17) C. corymbosa [64] C. curassavica [66] Root Cordiaquinone B (18) C. corymbosa [64] C. curassavica [66] C. linnaei [67] C. polycephala [68] Root Cordiaquinone C (19) C. corymbosa [64] C. linnaei [65] Root Cordiaquinone D (20) C. corymbosa [116] Root Cordiaquinone E (21) C. linnaei [67] C. polycephala [68] Root Cordiaquinone F (22) C. linnaei [67] Root Cordiaquinone G (23) C. linnaei [67] Root Cordiaquinone H (24) C. linnaei [67] Root Cordiaquinone J (25) C. curassavica [66] Root Cordiaquinone K (26) C. curassavica [66] Root Cordiaquinone L (27) C. leucocephala [69] C. polycephala [68] Root Cordiaquinone M (28) C. leucocephala [69] Root Cordiaquinone N (29)…”
Section: Meroterpenoid Naphthoquinonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, mitomycin C, in combination with other chemotherapeutic drugs, can show acceptable anticancer activities (Alkis et al, 2011;Kornek et al, 2004). Quinones have demonstrated a wide spectrum of activity via numerous mechanisms of action, specifically reactive oxygen species generation, DNA damage, uncoupling of oxidative phosphorylation protein, and inhibition of electron transporters (da Silva et al, 2011;Freitas et al, 2012;Wellington et al, 2019). Among them, versatile studies have shown the generation of semiquinone free radical after one-electron reduction of the quinones and active oxygen species during oxidation-reduction reactions involved in the mechanism of action (Bachur, Gordon, & Gee, 1977;Bayrak et al, 2019;Begleiter, 1985;Glazer, Hartman, & Richardson, 1982;Lown, Begleiter, Johnson, & Morgan, 1976;Lown, Sim, & Chen, 1978;Myers et al, 1977).…”
Section: Introductionmentioning
confidence: 99%